Disordered eating in elite youth athletes: A scoping review of studies published since 2000 - Marrows, M.; Grover, H.; Buckley, G.; Jeacocke, N. A.; Walton, C. C. (Journal of Science and Medicine in Sport Plus, 2023)
Objectives The purpose of this scoping review was to explore what is known about eating disorders and disordered eating in elite youth athletes aged 12-18. This review intended to explore what is known about the prevalence, risk factors, and outcomes of these conditions.